Charcot Neuropathic Arthropathy of the Foot: A Literature Review and Single-Center Experience - Tomas Kucera; Haroun Hassan Shaikh; Pavel Sponer (Journal of Diabetes Research)
Charcot neuropathic osteoarthropathy of the foot is a relatively common complication of diabetic neuropathy. Incorrect diagnosis and improper treatment often result in the extremity having to be amputated. This paper summarises the current view on the etiology, diagnostics, and treatment of diabetic Charcot neuropathic osteoarthropathy, with particular focus on preserving the extremity through surgical intervention from our own experiences.